Selective Regional Chemotherapy of Unresectable Hepatic Tumours Using Lipiodol. Issue 3 (1991) - Novell, J. R.; Dusheiko, G.; Markham, N. I.; Reddy, K.; Dick, R.; Hobbs, K. E. F.
Abstract : Over a 30 month period from 1987 to 1990, selective hepatic cannulation under fluoroscopic control was performed in 57 consecutive patients with primary and secondary malignancies of the liver. Fifty-three patients were subsequently treated using intra-arterial Lipiodol emulsified with epirubicin. The tumours treated were hepatocellular carcinoma (n = 35), metastatic adenocarcinoma (n = 14), intrahepatic cholangiocarcinoma (n = 3) and leiomyosarcoma (n = 1). For hepatocellular carcinoma the cumulative survival was 38% at one year; the median survival was 12.2 months for Stage I, 6.3 months for Stage II and 0.9 months for Stage III tumours. In metastatic disease the cumulative survival was 63% at one year. These data suggest that targeted intra-arterial chemotherapy with Lipiodol-epirubicin is a useful palliative therapy for patients with Stage and II HCC, and that a controlled trial of this treatment should be undertaken.